Aplicación del electromagnetismo en la levadura (saccharomyces cerevisiae) y su efecto antagónico in vitro frente a cepas de colletotrichum sp. y rhizopus sp. aisladas de frutos de papaya (carica papaya l.) - Llorente Vélez, Jean Antonio (2018)
He was to determine the effect of different intensities and exposure times of S. cerevisiae to electromagnetism and its effect on in vitro antagonistic activity against strains of Colletotrichum sp., and Rhizopus sp., isolated from papaya fruits (Carica papaya L.). Three intensities and three times of exposure to electromagnetism and witness. The influence of the factors on the production of biomass and how it exerted an effect on the antagonist activity of yeast against pathogens was evaluated. This date analyzes statistically evaluated with a completely random design with factorial arrangement (IxT + 1) with 10 treatments and 3 repetitions, where I correspond to magnetic field intensity and T to exposure time. The application of 45 gauss of intensity and 5 minutes of exposure of S. cerevisiae to electromagnetism exerted an effect on in vitro biomass, whereas 30 gausses of intensity and 10 minutes of exposure markedly activity antagonist in vitro against Colletotrichum sp., and Rhizopus sp.